Exploitation of E. coli for the production of penicillin G amidase: a tool for the synthesis of semisynthetic [beta]-lactam antibiotics - Sambyal, Krishika; Singh, Rahul Vikram (Journal of Genetic Engineering and Biotechnology, 2021)
Background Penicillin G amidase/acylases from microbial sources is a unique enzyme that belongs to the N-terminal nucleophilic hydrolase structural superfamily. It catalyzes the selective hydrolysis of side chain amide/acyl bond of penicillins and cephalosporins whereas the labile amide/acyl bond in the [beta]-lactam ring remains intact. Main body of abstract This review summarizes the production aspects of PGA from various microbial sources at optimized conditions. The minimal yield from wild strains has been extensively improved using varying strain improvement techniques like recombination and mutagenesis; further applied for the subsequent synthesis of 6-aminopenicillanic acid, which is an intermediate molecule for synthesis of a wide range of novel [beta]-lactam antibiotics. Immobilization of PGA has also been attempted to enhance the durability of enzyme for the industrial purposes. Short conclusion The present review provides an emphasis on exploitation of E. coli to enhance the microbial production of PGA. The latest achievements in the production of recombinant enzymes have also been discussed. Besides E. coli, other potent microbial strains with PGA activity must be explored to enhance the yields. Graphical abstract